Looking ahead or looking back: Current evaluations and the effect of psychological connectedness to a temporal self1. Issue 3 (13th January 2015) - Zhang, Meng; Aggarwal, Pankaj
Abstract: This research examines how consumers evaluate a target in the present that is positively associated with them in the past or future. We suggest that such evaluations are affected by the perceived connectedness between their current self and temporal self, that is, the self at that particular point in time of association with the target in the past or future. A strong (vs. weak) connectedness will result in a more (vs. less) favorable evaluation of the target—be it a product, brand, or pro‐social cause. Converging evidence supporting our premise is found in three studies.